Analysis of adaptive policy-based approach to avoid policy conflicts - Mansor, Amiraa Ali (2012)
PobMC is an adaptive scalable framework which uses policies to control and adapt the system behaviour. Moreover, PobMC has the capability to decouple the adaptation concerns from the application code. Since policies are used to govern the system behavior, conflicts may arise in the set of policies and also may arise during the refinement process, between the high-level goals and the implementable policies. Moreover, policy conflict can result from propagation, action composition and other constraint policies, which cannot be detected by simply comparing authorization policies. In this paper we present a static analysis to address the inconsistencies, scalability when there are two or more policies are enforced simultaneously. Then, we classify our system policy conflicts to verify that policies are enforced correctly. Moreover, the paper provides temporal specification patterns to detect each type of conflicts.